ОБ ИСПОЛЬЗОВАНИИ ПЕРМАНЕНТНЫХ GPS СТАНЦИЙ ДЛЯ ИОНОСФЕРНОГО МОНИТОРИНГА В ЗОНЕ РТ "УРАН-4" - Занимонский, Е. М.; Литвиненко, О. А. (Одеські астрономічні публікації, 2011)
Some results of study of correlation between the ionospheric scintillation index of cosmic radiosources on HF and total electron contents in ionosphere, measured by means of GPS-methods are submitted.